Analysis of Leadership Style on Employee Job Satisfaction Level at PT. Indofood CBP Sukses Makmur Tbk - Zidayatullah, Muhammad Hamid; Al Qowiy , Dafa Rasendriya; Wahjono, Sentot Imam (Manunggal Halim Jaya, 2025)
This study aims to analyze how the company's leadership style affects the level of job satisfaction of employees of PT Indofood CBP Sukses Makmur Tbk. An organization's leadership style significantly impacts employees' job satisfaction, which affects business performance. Based on the research findings, job satisfaction of PT Indofood CBP Sukses Makmur Tbk employees is positively and significantly influenced by transformational and transactional leadership styles. Job satisfaction can be improved by leaders who provide clear instructions, emotional support, and involve employees in decision-making. In addition, PT Indofood applies a mixture of participative and directive-supportive leadership philosophies, successfully creating a positive work atmosphere and increasing team member motivation and loyalty. The company prioritizes job satisfaction by creating a supportive environment through a fair appreciation system, clear regulations, proportional workload distribution, and appropriate incentives.